Peran Program Kampus Mengajar dalam Kompetensi Profesi Guru (Studi Penelitian Pada Mahasiswa Program Studi PBSI Universitas Negeri Makassar) - Hasnah Hasanuddin; Mayong Mayong; Usman Usman (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract: This study aims to determine how student's perception of the role of campus teaching program in the competence of the teaching profession (a research study on students of the Makassar State University PBSI study program). This research is a quantitative research. The research data are students' perceptions of the role of campus teaching programs. The research subjects were students of the PBSI study program who had attended the campus teaching program batches 1 – 3. The data collection technique was in the form of a survey using a questionnaire. Then, the analysis techniques used descriptive quantitative data analysis. The results showed that: (1) as 78 students' or 90% perceive the role of campus teaching program in pedagogic competence as being in the “high” category; (2) as 68 students' or 78% perceive the role of campus teaching program in personality competence as being in the “high” category; (3) as 75 students' or 86% perceive the role of campus teaching program in pedagogic competence as being in the “high” category; (4) as 70 students' or 80% perceive the role of campus teaching program in pedagogic competence as being in the “high” category.Keywords: Perception, campus teaching, teacher competence